Extension of a Function from the Exterior of an Interval to a Positive-Definite Function on the Entire Axis and an Approximation Characteristic of the Class W_M^r, β - Zastavnyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We establish sufficient conditions for the extension of a function defined on [a, +∞), where a > 0, to a positive-definite function on the entire axis.